Theoretical analysis of humidification – dehumidification process in an open type solar desalination system. (September 2018) - Hammadi, Salman H.
Abstract: A theoretical study of humidification – dehumidification (HDH) process in transient mode inside an open solar distiller is presented. Energy and mass balances of the water layer, airstream, and glass cover of the distiller are formulated and numerically simulated. Dry air enters into the distiller is heated up and humidified by solar radiation. When the glass temperature is lower than or equal to the dew point of the humid air, the vapor condenses on the inner side of the glass cover and runs down where the fresh water is collected. The results show that the productivity of fresh water is strongly affected by the water, air, and glass temperatures and the maximum productivity achieved in March was 2.2 kg/m 2 day. The increase in air velocity inside the solar distiller increases the evaporation rates and decreases the productivity. The distiller length required to reach the saturated state essentially depends on the air velocity and the water temperature. A comparison of the current analysis with other works showed a good agreement. Highlights: An open-type solar desalination system has been modeled. A theoretical analysis was performed in the transient mode. Effect of heat and mass transfer characteristics in a solar distiller was estimated. Fresh water production was calculated throughout year.